Depopulation of Edge States under Local Periodic Driving despite Topological Protection - Jor, Christina; Cherpakova, Zlata; Dauer, Christoph; Letscher, Fabian; Fleischhauer, Michael; Eggert, Sebastian; Linden, Stefan; Von Freymann, Georg (2019 Conference on Lasers and Electro-Optics, CLEO 2019 - Proceedings, 2019)
We show that edge states can be depopulated despite their topological protection. Local time-periodic driving results in hybridization of edge and bulk states for certain driving frequencies. Experiments are performed using plasmonic and dielectric waveguides.
CRIS-Team Scopus Importer:2023-03-27